When tuberculosis comes back: who develops recurrent tuberculosis in california? - Lisa Pascopella; Kathryn Deriemer; James P Watt; Jennifer M Flood (PLoS ONE, 2011)
Recurrent tuberculosis suggests potentially modifiable gaps in tuberculosis treatment and control activities. The frequency of late recurrences following treatment completion has not been well-studied. We determined the frequency of, and risk factors associated with, tuberculosis that recurs at least one year after completion of anti-tuberculosis therapy in California.The study population included culture-positive, pulmonary tuberculosis patients reported to the California tuberculosis case registry from 1993 to 2007 who completed anti-tuberculosis therapy. A person with late recurrent tuberculosis was defined as an individual that appeared in the registry more than once, determined by match on name and date-of-birth, with at least one year between treatment completion of the first episode and treatment initiation of the second episode.Among 23,517 tuberculosis patients, 148 (0.63%) had a late recurrence. Independent risk factors for recurrence included: infection with a pyrazinamide mono-resistant isolate (adjusted hazard ratio, 2.93; p = 0.019); initiation of an isoniazid- and rifampin-only treatment regimen (adjusted hazard ratio, 2.55; p = 0.0412); sputum smear-positive disease (adjusted hazard ratio, 1.96; p = 0.0003); human immunodeficiency virus infection (adjusted hazard ratio, 1.81; p = 0.0149); and birth in the United States (adjusted hazard ratio, 1.88; p = 0.0002). Infection with an isoniazid mono-resistant isolate was protective (adjusted hazard ratio, 0.25; p = 0.0171).The low frequency of late recurrent tuberculosis in California suggests that local TB control programs are largely successful at preventing this adverse outcome. Nonetheless, we identified subpopulations at increased risk of late tuberculosis recurrence that may benefit from additional medical or public health interventions.